THE EFFECT OF LIQUIDITY AND COMPANY SIZE ON FINANCIAL DISTRESS WITH COMPANY VALUE AS A MEDIATING VARIABLE IN TRANSPORTATION AND LOGISTICS COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR PERIOD 2021-2023 - Kamilah, Hayatun Nufus; Indira, Irma (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to examine the effect of liquidity and company size on financial distress, with company value as a mediating variable in transportation and logistics companies listed on the Indonesia Stock Exchange for the period 2021-2023. The sampling was conducted using purposive sampling, resulting in a sample of 14 companies with financial report data from 42 companies over three years of observation. SmartPLS 3 is the software used in this research, which cinsists of descriptive statistical analysis, outer and inner model analysis, and hypothesis testing. The results of this study indicate that liquidity and company value significantly affect financial distress. Company size does not have a significant impact on financial distress. Additionally, liquidity and company size do not affect company value. Furthermore, company value does not effectively mediate the influence of liquidity and company size on financial distress in transportation and logistics companies listed on the Indonesia Stock Exchange for the period 2021-2023. Keywords: Liquidity; Company Size; Financial Distress; Company Value